1995
DOI: 10.2337/diab.44.12.1369
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Islet GLUT2 Glucose Transporter mRNA and Protein Expression in Humans With and Without NIDDM

Abstract: GLUT2 glucose transporter mRNA has been shown to be underexpressed in pancreatic islets of numerous animal models of non-insulin-dependent diabetes mellitus (NIDDM). It has been proposed that this molecular defect contributes to the pathogenesis of diabetes, although information concerning the expression of GLUT2 in human pancreatic islet tissue is lacking. In contrast to the high abundance of GLUT2 in rat islets, human islets were found to express distinctly low levels of this glucose transporter mRNA and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 0 publications
1
28
1
2
Order By: Relevance
“…The techniques used here are not quantitative so do not permit estimation of relative amounts of GLUT1 and GLUT2 in our tissue samples. Nevertheless, the results do suggest that GLUT1 is the major beta cell glucose transporter in fetal and neonatal life and, although we clearly demonstrate that GLUT2 can be detected in the mature pancreas, other studies show that GLUT1 remains the major isoform in the adult pancreas [5,6].…”
Section: Discussioncontrasting
confidence: 77%
“…The techniques used here are not quantitative so do not permit estimation of relative amounts of GLUT1 and GLUT2 in our tissue samples. Nevertheless, the results do suggest that GLUT1 is the major beta cell glucose transporter in fetal and neonatal life and, although we clearly demonstrate that GLUT2 can be detected in the mature pancreas, other studies show that GLUT1 remains the major isoform in the adult pancreas [5,6].…”
Section: Discussioncontrasting
confidence: 77%
“…In endocrine pancreas ␤ cells, the predominant glucose-sensor has been definitively identified as glucokinase by knock out of the gene in mice (32,33), and the significance of the specific GLUT 2 expression in rodent ␤ cells is still disputed, especially as the amount of the GLUT 2 isoform seems to be very low in human ␤ cells (34,35). German (36) has shown that ␤ cells overexpressing GLUT 1 do not lose their ability to sense changes in glucose concentration within the physiological range and to respond by an appropriate stimulation of the insulin gene promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Human beta cells could be more resistant to the toxic action of streptozotocin and alloxan either because they express the GLUT2 glucose transporter only to a very low extent [7,8] (1-2% of the level expression in rat beta cells), or, alternatively, because streptozotocin and alloxan, in contrast to the rat GLUT2 glucose transporter isoform, are not taken up through the human GLUT2 glucose transporter isoform into the intracellular compartment where the toxins exert their cell-death action.…”
Section: Mechanism Underlying Resistance Of Human Pancreatic Beta Celmentioning
confidence: 99%
“…The results show that it is apparently the very low level of constitutive GLUT2 glucose transporter expression in the human beta cell [7,8] rather than the inability of the human GLUT2 glucose transporter isoform to provide uptake of streptozotocin and alloxan into the intracellular compartment (Table 1) which is responsible for the extraordinarily high resistance of humans against the diabetogenic action of streptozotocin and alloxan. However, even if the human GLUT2 glucose transporter isoform would be more abundant in human pancreatic beta cells, the lower capacity for uptake of the toxins through the human GLUT2 glucose transporter isoform as compared to the rat transporter isoform would limit Therefore it is also not surprising that development of Type 1 diabetes mellitus is not known to be a typical side effect when streptozotocin is used as a chemotherapeutic agent in human cancer treatment and that it is not a particularly efficient anti-cancer drug when used in the treatment of human insulinomas which usually do not express the GLUT2 glucose transporter [4].…”
Section: Mechanism Underlying Resistance Of Human Pancreatic Beta Celmentioning
confidence: 99%